The renaissance of American Indian higher education : capturing the dream - Ah Nee-Benham, Maenette K. P. (Maenette Kapeʻahiokalani Padeken), 1956-; Stein, Wayne J., 1950- (Lawrence Erlbaum, 2003)
The Native American Higher Education Initiative (NAHEI), a W.W. Kellogg Foundation project, has supported the development and growth of centers of excellence at Tribal Colleges and Universities across the United States. These are centers of new thinking about learning and teaching, modeling alternative forms of educational leadership, and constructing new systems of post-secondary learning at Tribal Colleges and Universities. This book translates the knowledge gained through the NAHEI programs into a form that can be adapted by a broad audience, including practitioners in pre-K through post-se.
Keywords: Indians of North America -- Education (Higher) -- United States.; Indian universities and colleges -- United States.; Universités des Peuples autochtones -- États-Unis.; EDUCATION -- Higher.; Indian universities and colleges; Indians of North America -- Education (Higher); United States